Functional Energy Accumulation, Photo- and Magnetosensitive Hybridity in the GaSe-Based Hierarchical Structures - Piotr Chabecki; Dariusz Całus; Fedir Ivashchyshyn; Anna Pidluzhna; Orest Hryhorchak; Ihor Bordun; Oleksandr Makarchuk; Andriy V. Kityk (Energies, 2020)
We report on the complex GaSe-based hierarchical structures GaSe(CS(NH2)2), GaSe(SmCl3) and GaSe(CS(NH2)2(SmCl3)) synthesized by an intercalation method. The conductive properties of synthesized clathrates and their relation to hierarchical structural complexity were explored by an impedance spectroscopy technique. The impedance response, thermostimulated discharge spectra, and photo- and magnetoresistive effects are reported. Based on the obtained results, the impurity energy spectra were calculated. A strong low-frequency inductive response, observable in the GaSe(SmCl3) clathrate, makes this material promising for the development of gyrator-free nanodelay lines potentially applicable in nanoelectronics. Hierarchical GaSe(CS(NH2)2(SmCl3)) clathrate, on the other hand, reveals hysteresis of the current–voltage characteristics, apparently confirming an accumulation of electric energy at interphase boundaries. A relevant spin battery effect, observable experimentally in stationary magnetic fields, demonstrates a principal possibility of the electric energy accumulation at a quantum level.